The Effectiveness of the Implementation of the New Student Admissions Policy Through the Zoning System at the Education and Culture Office of Gorontalo Regency - Wahyuni Ibrahim; Arifin Tahir; Frista Iin Wahyuni (Jurnal Ilmu Manajemen dan Bisnis, 2021)
The purpose of this research is: (1) to identify and analyze the effectiveness of the implementation of the new student admission policy through the zoning system at the Education and Culture Office of Gorontalo Regency, (2) to find out and analyze what factors influence the effectiveness of the implementation of the new student admission policy through the zoning system at the Education and Culture Office of Gorontalo Regency. The approach used in this research is qualitative approach. This research was conducted at the Education and Culture Office of Gorontalo Regency. The data sources used are primary and secondary data. The primary data for this research is data obtained directly from research objects and processed by researchers themselves. The informants in this study were: Head of The Education and Culture Office of Gorontalo Regency, Secretary, Head of Basic Education, Head of Student section and Curriculum, and parents of students. Meanwhile, secondary data for this research comes from related data sourced from previous research data and from agencies related to the variables studied. Data collection techniques both primary and secondary data are carried out through in-depth interviews. The results showed that: The effectiveness of implementing a policy is fulfilled if (1) there is clarity of strategy for achieving goals, the policy is a decision taken by an institution to solve a problem or to achieve a certain goal. In implementing this policy, it is based on the implementation goal of admitting students through the zoning system, namely providing opportunities for school-age citizens to obtain quality education services and encouraging increased access to education services. (2) Well-prepared planning, planning is finding, developing, and analyzing possible directions of action. With a well-structured and coordinated plan, the objectives of the policy are easy to fulfill. (3) The Effective Implementation, and (4) supervision.